Pengaruh Ekspor Industri Migas dan Investasi Asing Langsung (FDI) Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 1983-2023: The Effect of Oil and Gas Industry Exports and Foreign Direct Investment (FDI) on Economic Growth in Indonesia 1983-2023 - Diandra Damayanti, Dea; Putri, Fitri Noviyana; Tirtana, Dodi (Universitas Bojonegoro, 2025)
This study aims to analyze the impact of oil and gas industry exports (EIM) and foreign direct investment (FDI) on Indonesia's economic growth. The research uses time series data spanning from 1983 to 2023, obtained from the Central Statistics Agency and the World Bank. The analysis method employed is multiple linear regression. The results indicate that oil and gas exports have a significant positive effect on economic growth. In contrast, foreign direct investment (FDI) has a significant negative impact on economic growth. This finding differs from the general view and most previous studies that suggest FDI promotes economic growth, especially in developing countries. The implications of this study highlight the need to strengthen the oil and gas export sector as a driver of economic growth and to implement selective policies toward FDI, ensuring that foreign investment is directed toward productive sectors capable of supporting sustainable economic development and providing tangible benefits to national progress